Prof. Lunxu Liu: the demand for surgery will only go up instead of down - Gao, Chen; Li, Brad (Journal of Thoracic Disease; Vol 10, No 12 (December 30, 2018): Journal of Thoracic Disease, 2018)
The 3rd Ruijin International Thoracic Symposium was held in Shanghai from November 15–16, 2018. With a focus on the latest advances of minimally invasive treatment of thoracic cancers, the symposium brought together numerous top national and international experts to discuss and exchange ideas on a series of hot topics in the field of thoracic surgery.